Educational Game Making Training (Wordwall Game) for Teachers at MI Hidayatul Mubtadiin Wates Sumbergempol Tulungagung - Ivantri, Rohmah (Indonesian Journal of Advanced Social Works, 2024)
The return of face-to-face learning after the era of online learning triggered by the pandemic brings new challenges for teachers and students. Accompanied by the launch of the Merdeka Belajar Curriculum, teachers need to re-adapt their teaching methods to suit the ongoing learning conditions. A training program on the use of Wordwall as a creative evaluation medium for teachers at MI Hidayatul Mubtadiin Wates, Tulungagung, using the Asset Based Community Development (ABCD) approach. This program aims to improve teacher competence in creating interesting and innovative learning evaluations, by integrating technology into the learning process. The training involves observation, interviews, and direct practice in creating educational games based on Wordwall. The evaluation results show that this training is effective in improving teacher skills in creating creative and interesting learning media for students.